Die Blau’schen Steine und der „Priesterfürst“ im Netzrock - Boese, Johannes (Altorientalische Forschungen, 2010)
The so-called Blau Monuments (“Blau’sche Steine”) are conventionally dated to the Jemdet Nasr Period (“Uruk III”), but recent researches have shown that their inscriptions must belong to the beginning of the Early Dynastic Age (ED I). Since the main figure of the relief decoration on the monuments, the “priest-king” with net-skirt, is virtually identical with the pictorial representations of the same person on a lot of cylinder seals, which have been dated unanimously until now to the later Protoliterate (“Early Sumerian”) Period, there arises a crucial question: Do these seals – and perhaps also the famous Warka-Vase with comparable pictures – equally stem, like the Blau Monuments, from the next younger phase (ED I), or did there possibly exist an unbroken tradition in theme, style, and iconography, reaching from the last phase of the Protoliterate to the first stage of the Early Dynastic Period? The first named alternative seems to me the more probable answer, though it cannot be proved definitely.